Naturally Based Biomaterials and Therapeutics The Case of India - Eswarappa, Veda. (SpringerBriefs in Public Health,, 2013)
This book advances biomedical innovations to address the plethora of health problems afflicting the developing world. A panoply of cultural, economic, infrastructural, and other factors prevent many interventions currently popular in the developed world from being similarly effective in the developing world. This book discusses less-traditional approaches, such as naturally based biomaterials and therapeutics, an area that has traditionally been overlooked but has also demonstrated impressive potential for health applications in recent years. This book explores precisely the kinds of applications which can enable countries like India to access more effective, inexpensive treatments while also taking more ownership of their healthcare technologies and innovations.